(untitled) (Journal of Hama University, 2025)
In this research, the most suitable modulation strategy for operating the cascaded multilevel inverter was identified by explaining the control system of the multilevel inverter and testing three different strategies for generating gate pulses for the power electronics components. The best strategy among them was determined. The operation of the single-phase cascaded inverter and the method of generating gate pulses were simulated using Matlab/Simulink. Additionally, the inverter circuit was practically implemented, and the necessary tests were conducted to identify the best modulation strategy. The results demonstrated the superiority of the Phase Opposition Disposition (POD-PWM) strategy, as it resulted in the lowest total harmonic distortion (THD) in the voltage waveform compared to the other strategies, especially at different carrier wave frequencies. Furthermore, the effect of the number of voltage levels on the THD rate was studied. The results showed that the lowest total harmonic distortion rate for the single-phase seven-level cascaded inverter voltage waveform was achieved using the POD modulation strategy with a modulation frequency of 3000 Hz, where the total harmonic distortion value was 17.12%.